PENGARUH MIKROBA DAN UREA TERHADAP PERTUMBUHAN DAN HASIL JAGUNG PADA TANAH GAMBUT - Etes, Fernando; Zulfita, Dwi; Anggorowati, Dini (Jurnal Sains Mahasiswa Pertanian, 2013)
This study aims to determine the best dose of N fertilizer for corn growth and yield double inoculated with mycorrhizal fungi and Azospirillum arbuskula peat soils. research was conducted in the experimental garden Tanjungpura pontianak university agricultural faculty from 10 november 2011 to 31 January 2012.study using completely randomized design (CRD) with 2 factors factorial treatments and 3 replications. every combination treatment plant consists of 3 samples. The first factor is microbial inoculation (M) and the second factor is the factor of urea (U). treatment are: microbial inoculation factor (M) consists of 4 stage are: Mo = without inoculation, M1 = mycorrhizal inoculation arbuskula, M2 = inoculation of bacteria fastening non-symbiotic N Azospirillum lipoferum, M3 = inoculation with mycorrhizal and bacterial arbuskula fastening N non-symbiotic Azospirillum lipoferum. factor urea (U) consists of 4 standard, namely: U0 = without fertilizer urea, urea U1 = 1/4 the recommended dose = 1.56 g / polybag, U2 = urea 1/2 the recommended dose = 3.13 g / polybag and U3 = urea appropriate recommended dose = 6.25 g / polybag. observed variables in this study were plant height (cm), number of leaves (pieces), leaf chlorophyll content (SPAD units), plant dry weight (g), leaf area (cm), N and P uptake (g), root infection by mycorrhizae (%) and dry shelled (g).the results showed that microbial inoculation and urea fertilizers provide the same effect on the number of leaves weeks 2, 4, 6 and 8 after planting, plant height 2 and 8 weeks after planting and has the best. provision of urea at various doses affect the levels of chlorophyll and leaf area dau total. interactions between microbial inoculation and urea fertilizers provide a good influence on root infection, P and N uptake, plant dry weight. The combination of microbial inoculation + 1.56 g urea (the recommended dose) resulted in infection of the roots, uptake of N and P on corn the best. corn plants without giving urea producing chlorophyll content of leaves and leaf area at its best. interaks without microbial inoculation and without urea producing plant dry weight is best. maize plants inoculated with mycorrhiza and Azospirillum double generating plant height to 4 and 6 weeks after planting is best. results of dry shelled corn crop ever produced in double inoculation with mycorrhiza and Azospirillum without giving urea. Keywords: microbes, urea, growth, yield, corn, peat